Improvement of Learning Outcomes of The Qur'an Hadith by Using The Inquiry Learning Model of Piety Material In Madrasah Ibtidaiyah - Zaenal Arifin (FITK UIN Walisongo Semarang, 2024)
This research aims to improve the learning outcomes of the Qur'an Hadith by using the Inquiry Learning model of Takwa material at Madrasah Ibtidaiyah. Learning the Qur'an Hadith material of Piety in grade IV of MI Al Hidayah Langon Jepara using the Inquiry Learning method has proven to be effective in improving student learning outcomes. This study uses the Classroom Action Research (PTK) method which involves four stages: planning, action, observation, and reflection. Each cycle is carried out repeatedly with a focus on the application of the Inquiry Learning method. The results of the study show that this method significantly improves students' understanding of Takwa material. In the pre-cycle, the average score of students only reached 58.40, indicating that understanding was still low. However, after the application of the Inquiry Learning method, the average score of students increased gradually in the first cycle (69.42), the second cycle (80.07), and the third cycle (85.07), which showed a significant increase until it reached the high category. This increase illustrates the effectiveness of the Inquiry Learning method in helping students achieve a deeper understanding of the material being taught. The learning outcomes of students who exceeded the KKM target by 85% showed that this method was very suitable to be applied in learning the Qur'an Hadith, especially in the material of Piety. Thus, the application of the Inquiry Learning method in learning at MI Al Hidayah Langon Jepara can be considered successful and make a positive contribution to improving the quality of education, especially in the subject of Al-Qur'an Hadith. This proves that an active and participatory approach to learning can bring significant results.